Revisiting JMLA case reports: a publication category for driving innovation in health sciences librarianship - Jill T. Boruff, AHIP; Michelle Kraft; Alexander Carroll (Journal of the Medical Library Association)
In the April 2019 issue (Vol. 106 No. 3), the Journal of the Medical Library Association (JMLA) debuted its Case Report publication category. In the years following this decision, the Case Reports category has grown into an integral component of JMLA. In this editorial, the JMLA Editorial Team highlights the value of case reports and outlines strategies authors can use to draft impactful manuscripts for this category.